The Meaning Of The Message Of Optimism In The Lyrics Of Yura Yunita's Song "Batin Speech" - Mukharomah, Hidayatul; Muyasaroh, Siti (Jurnal Sosial Sains dan Komunikasi, 2023)
This study aims to find out the meaning of the message in a song "Inner Speech" by Yura Yunita. This study uses Rolland Barthes' semiotic theory. In a communication, meaning means understanding that objects not only carry information, but also constitute a structured system of signs. Based on the book Culturan and Communication Studies, the core of Barthes' theory is the idea of ​​two orders of signification consisting of denotation, connotation and myth (Fiske, 2007). Yunita uses descriptive qualitative research methods. The data collection technique used is document study, that is, data acquisition is achieved through tracing various sources which are predicted to contain the data needed in this study. The researcher did not conduct interviews with related parties because in Semiotics documents in the form of song lyrics will be analyzed in depth based on the interpretation of the researcher using Rolland Barthes' Semiotics analysis technique. The results of this study indicate that the lyrics of the song Tutur Batin by Yura Yunita contain several messages of optimism, confidence, hope and others